Phenotypic MicroArray (PM) profiles (carbon sources and sensitivity to osmolytes and pH) of Campylobacter jejuni ATCC 33560 in response to temperature - Tang, John Yew Huat; Carlson, J.; Mohamad Ghazali, Farinazleen; Abdul Aziz, Saleha; Nishibuchi, Mitsuaki; Nakaguchi, Yoshitsugu; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
The present study aimed to provide an insight of C. jejuni ATCC 33560 phenotype profiles (carbon sources and sensitivity to osmolytes and pH) using Phenotypic MicroArray (PM) system in response to optimal and suboptimal temperature. C. jejuni ATCC 33560 showed utilization carbon sources from amino acids and carboxylates but not from sugars. C. jejuni ATCC 33560 is sensitive to NaCl at 2% and above but showed survival in a wide range of food preservatives (sodium lactate, sodium phosphate, sodium benzoate, ammonium sulphate and sodium nitrate). When incubated at suboptimal temperature, no phenotype loss was observed in carbon source plates. Phenotype loss of C. jejuni ATCC 33560 was observed in sodium chloride (1%), sodium sulphate (2-3%), sodium formate (1%), sodium lactate (7-12%), sodium phosphate pH7 (100mM and 200mM), ammonium sulphate pH8 (50mM), sodium nitrate (60mM, 80mM and 100mM), sodium nitrite (10mM), and growth in pH5. The phenotypic profile from present study will provide a better insight related to survival of C. jejuni ATCC 33560.